(untitled) (Materiali di Estetica. Terza serie, 2014)
Merleau-Ponty is one of the very first philosophers who devoted a reflection to the seventh art: he outlined a convergence between contemporary philosophy and cinema, insofar as phenomenology and cinematographic expression shares a common vocation to “make us see the bond between subject and world, between subject and others, rather than to explain it” (The Film and the New Psychology). As Christian Metz observes, thanks to Merleau-Ponty, an entire generation of filmmakers and critics had been initiated to phenomenology and to a new comprehension of cinema. But such connection between film theory and phenomenology is not confined to an epoch or historical conjuncture: in the last two decades, the dialogue between cinema and phenomenology has originated a field of studies, which is more and more productive and fruitful. This essay aims at deepening such perspective by approaching the fundamental work of Vivian Sobchack. Drawing on phenomenology and Merleau-Ponty’s philosophy, the American cinema and media theorist has developed an original and rich reflection, which in Italy is still almost unknown. KEYWORDS: esperienza filmica; embodiment; Sobchack; Merleau-Ponty;